2018
DOI: 10.1073/pnas.1720897115
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of AID/APOBEC-like deaminases in metazoa: multiplicity of clades and widespread roles in immunity

Abstract: SignificanceMutagenic AID/APOBEC deaminases (AADs) are central to processes such as generation of antibody diversity and antiviral defense in vertebrates. Their presence and role outside vertebrates are poorly characterized. We report the discovery of several AADs, including some that are secreted, across diverse metazoan, dictyosteliid, and algal lineages. They appear to have emerged from an early transfer of an AAD from bacterial toxin systems, followed by extensive diversification into multiple eukaryotic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 74 publications
1
84
0
Order By: Relevance
“…The APOBEC3 family of AID paralogues also restrict viral infection by deaminating viral genomes; UNG2 and APE activities downstream of APOBEC3 can contribute to viral restriction (49,50). AID/APOBEC-like deaminases occur across metazoa, dictyosteliida, and even algae, and may have evolved in an arms race with viruses and retro elements (51). Here, we've shown that SAMHD1 is another virus restriction factor that contributes to the mutagenicity of AID-by promoting transversion mutation downstream of AID.…”
Section: Similarities Between Ig Hypermutation and Intracellular Virumentioning
confidence: 81%
“…The APOBEC3 family of AID paralogues also restrict viral infection by deaminating viral genomes; UNG2 and APE activities downstream of APOBEC3 can contribute to viral restriction (49,50). AID/APOBEC-like deaminases occur across metazoa, dictyosteliida, and even algae, and may have evolved in an arms race with viruses and retro elements (51). Here, we've shown that SAMHD1 is another virus restriction factor that contributes to the mutagenicity of AID-by promoting transversion mutation downstream of AID.…”
Section: Similarities Between Ig Hypermutation and Intracellular Virumentioning
confidence: 81%
“…Some of these have predicted signal peptides suggesting that they are secreted (e.g., in Caenorhabditis remanei and Entamoeba). The combination of lineagespecific expansions, rapid evolution, and secretion is a hallmark of proteins that are deployed as effectors in defensive or offensive roles in biological conflicts (Krishnan et al 2018;Zhang et al 2016;Lespinet et al 2002). In light of this we hypothesize that several eukaryotic Smr proteins, 12 290 295 300 305 310 especially the expanded versions, might function beyond translation surveillance as effectors deployed against viral or parasitic RNA.…”
Section: Evolution Of Nonu-1 and Smr-domain Proteinsmentioning
confidence: 99%
“…RNA editing refers to specific modifications in an RNA molecule that result in alterations of the RNA sequence compared to the one encoded by the genome. RNA editing events occur in all eukaryotes, although the molecular mechanisms are taxon dependent and may involve different enzymes, leading to different RNA modifications, particularly between plants and animals [25,26]. For instance, substitutional RNA editing is a mechanism occurring across all metazoans, and this process is characterized by nucleotide modification mediated by deaminases of, principally, two distinct families.…”
Section: Editing Of Mirnamentioning
confidence: 99%